Association of Individual Characteristic and Blood Pressure with Prevalence of Diabetes Mellitus - Adriansyah, Agus Aan; Firdausi, Nurul Jannatul (International Journal of Psychosocial Rehabilitation, 2020)
In Indonesia, diabetes mellitus (DM) is a serious threat to health development because it can lead to blindness, kidney failure, foot diabetes, heart disease and stroke. In 2018, there were 4.434 total patients with DM who went for outpatient treatment at the Sidoarjo Regional Hospital. This number is still lower when compared to 2017, which is 5.262 sufferers. However, more worryingly, patients who are found to be younger. The purpose of this study is to analyze the individual characteristics and blood pressure with diabetes disease incidence. This type of research is an analytical study using a cross-sectional approach. The population was all villagers in Balongtani with the required sample size of 70 respondents. The sampling technique was done by purposive sampling. Data obtained by using questionnaires and analyzed using a chi-square test with alpha 0.05. The result showed that there was a significant relationship between age and DM (p = 0.001), between the sexes and DM (p = 0.001), also between smoking and DM (p = 0.002) as well as there was a significant relationship between blood pressure and DM incidence (p = 0.016). The conclusion of this study is people age more than 50 years would have a risk of DM 0,03x. Women will be at risk of DM up to 0.077x. People who have a history of smoking, especially active smoking can be at risk of developing DM. S Seorang who have a history of hypertension would be at risk of developing DM by 9x. Things that need to be considered are the need to emphasize promotive and preventive efforts to prevent DM and various risk factors. Always maintain a healthy lifestyle, do not smoke and maintain the dietary habit.